Validation of GOME total ozone by means of the Norwegian ozone monitoring network - Hansen, G.; Dahlback, A.; Tønnessen, F.; Svenøe, T. (Annales Geophysicae, 1999)
The Global Ozone Monitoring Experiment (GOME) onboard the ERS-2 satellite has been in operation since July 1995. The Norwegian ground-based total ozone network has played an important role both in the main validation during the commissioning phase and in the validation of upgraded versions of the analysis algorithms of the instrument. The ground-based network consists of various spectrometer types (Dobson, Brewer, UV filter instruments). The validation of the second algorithm version used until January 1998 reveals a very good agreement between GOME and ground-based data at solar zenith angles <60° and deviations of GOME total ozone data from ground-based data of up to ±60 DU (~20%) at zenith angles >60°. The deviations strongly depend on the season of the year, being negative in summer and positive in winter/spring, The deviations furthermore show a considerable scattering (up to ±25 DU in monthly average values of 5° SZA intervals), even in close spatial and temporal coincidence with ground-based measurements, especially in the high Arctic. The deviations are also dependent on the viewing geometry/ground pixel size with an additional negative offset for the large pixels used in the backswath mode and at solar zenith angles >85°, compared to forward-swath pixels. Key words. Atmospheric composition and structure (middle atmosphere · composition and chemistry; instruments and techniques)